2012
DOI: 10.1055/s-0032-1315111
|View full text |Cite
|
Sign up to set email alerts
|

New Monoterpenes, Diterpenes, and Lignans from Abies recurvata

Abstract: From the aerial part of Abies recurvata, 62 miscellaneous chemical constituents were isolated including 6 new and 56 known ones. The new compounds comprised three monoterpenes, two diterpenes, and one lignan. Their chemical structures were characterized on the basis of various spectroscopic techniques. Dihydrodehydrodiconiferyl alcohol (35) showed the strongest inhibitory effects against lipopolysaccharide-induced nitric oxide production in RAW 264.7 cells with an IC₅₀ value of 66.4 µM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Thus, compound 3 was elucidated as trans-linalool-3,6-oxide-β-D-glucopyranoside. Its 1 H and 13 C NMR data were identical to those reported in the literature (Table 2) [11].…”
Section: Structure Elucidationsupporting
confidence: 81%
“…Thus, compound 3 was elucidated as trans-linalool-3,6-oxide-β-D-glucopyranoside. Its 1 H and 13 C NMR data were identical to those reported in the literature (Table 2) [11].…”
Section: Structure Elucidationsupporting
confidence: 81%
“…By NMR data analysis and comparison with the reported spectroscopic data, eight known compounds were identified as cyclamiretin A (2), [15] psychotrianoside G (3), [16] 3-hydroxy-β-damascone ( 5), [12] megastigmane ( 6), [17] corchoionol C (7), [18] zingiberoside B (9), [19] angelicoidenol (10), [19] trans-linalool-3,6-oxide-β-D-glucopyranoside (11). [20] At present, most of epoxy moiety in oleanolic-type triterpene existed at C-11 and C-12. In this study, we reported a novel oleanolic-type triterpene from A. crispa with a rare 15,16-epoxy system.…”
Section: Structural Elucidationmentioning
confidence: 99%